Stunting Problems in Pregnant Women and Children Within 1000 Days of Early Life - Syukur, Sabirin B.; Harismayanti, Harismayanti (International Journal Papier Advance and Scientific Review, 2020)
Pregnant women need nutrients and minerals to support fetal development and metabolic processes because pregnant women are prone to nutritional problems. This study aims to analyze the problem of stunting in pregnant women and children within the first 1000 days of life. This type of research uses a descriptive quantitative approach using analytical survey methods and interviews as well as direct observation of baduta with stunting problems. The sample in this study was conducted using purposive sampling technique with a sample size of 80 Baduta. The results showed the description of mother’s knowledge of the problem of stunting in Baduta. Based on table 3 above, there were 47 baduta (86.7%) non-stunted mothers (11.3%). Meanwhile, there were 17 baduta (63.0%) stunting children and 10 baduta (37.0%) children who were not stunted. Several causes that affect children’s nutrition that can be at risk and lead to stunting problems, namely low mother’s education, lack of knowledge, lack of family income, history of KEK, incomplete immunization, not getting complementary breastfeeding